2016
DOI: 10.1097/md.0000000000005599
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of platinum plus gemcitabine (PG) chemotherapy with or without molecular targeted agent (MTA) in first-line treatment of non-small cell lung cancer (NSCLC)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Blood disorders were more frequently reported in the control group. As anemia is frequently reported as a result of applied chemotherapy and/or targeted therapy [ 18 ] it could explain the increased rate in the control group. In addition, thromboembolic events and hemorrhage were documented for bevacizumab in combination with CTx [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood disorders were more frequently reported in the control group. As anemia is frequently reported as a result of applied chemotherapy and/or targeted therapy [ 18 ] it could explain the increased rate in the control group. In addition, thromboembolic events and hemorrhage were documented for bevacizumab in combination with CTx [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thromboembolic events and hemorrhage were documented for bevacizumab in combination with CTx [ 10 ]. Gastrointestinal adverse events have been reported to be increased in patients during mAb, targeted, or ICI therapy [ 9 , 10 , 11 , 18 ] and may explain the higher percentage of these events in the control group. Accordingly, as to diarrhea the incidence was reported to be elevated in combined CTx/mAb [ 11 ] and CTx/targeted therapy [ 18 ] compared to CTx alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guillermo et al first showed that hydroxylated pyrrolidine represents a SAH/MTA inhibitor and speculated that these compounds might be transitional analogs (76). However, inhibition of Pfs is fatal to cells because the accumulation of MTA and SAH is toxic to cells (77,78). Excess MTA levels in cells inhibit growth processes and DNA synthesis by indirectly preventing the synthesis of polyamines involved in these important processes (79,80).…”
Section: Target the Luxs/al-2 System: New Antibacterial Strategy For mentioning
confidence: 99%
“…It is known that these drugs are given based on the performance status and age of the patient. Adverse effects are severe in several patients, and hospitalization is also necessary if these occur 20,21. In a recent study, it was proposed that a single agent or avoidance of platinum analogs for the elderly aged ≥70 years could be a solution 21.…”
Section: Discussionmentioning
confidence: 99%